1999
DOI: 10.1007/s002340050863
|View full text |Cite
|
Sign up to set email alerts
|

Unusual MRI findings in lymphocytic hypophysitis with central diabetes insipidus

Abstract: We report an unusual case of lymphocytic hypophysitis, which proved to be cystic at surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 4 publications
0
6
1
Order By: Relevance
“…25 Cystic appearance was described in 5% of the patients with LYH. 1,8,11,12,[26][27][28][29][30][31][32][33][34] Homogeneous enhancement can also be observed in pituitary adenomas. 35 On the other hand, parasellar T2 dark sign was a characteristic finding in LYH and can contribute to distinguishing pituitary LYH from adenoma with certainty.…”
Section: Discussionmentioning
confidence: 99%
“…25 Cystic appearance was described in 5% of the patients with LYH. 1,8,11,12,[26][27][28][29][30][31][32][33][34] Homogeneous enhancement can also be observed in pituitary adenomas. 35 On the other hand, parasellar T2 dark sign was a characteristic finding in LYH and can contribute to distinguishing pituitary LYH from adenoma with certainty.…”
Section: Discussionmentioning
confidence: 99%
“…Since Farah et al first reported cystic lymphocytic hypophysitis, only 5 cases of cystic lymphocytic hypophysitis and 2 cases of cystic granulomatous hypophysitis have been described, while Puchner et al reported 3 cases of lymphocytic hypophysitis with cystic craniopharyngioma [7][8][9]26]. Although the evidence of Rathke's cleft cyst or craniopharyngioma such as columnar epithelial layers or squamous metaplasia was not found in our case, the possibility remains that the histological findings of this patient's pituitary tissue may be the secondary changes caused by some other cystic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis of this entity should be made by histological findings characteristic of massive infiltration of lymphocytes and plasma cells followed by necrosis or surrounding parenchymal fibrosis [5,6]. Previously reported cases of lymphocytic hypophysitis have nonspecific, solid enlargement of the pituitary gland but only 5 cases of cystic lymphocytic hypophysitis have been described in English literature [7][8][9].…”
mentioning
confidence: 99%
“…The most unique and prominent MRI features are the pituitary stalk thickening and marked enlargement of the pituitary gland with homogeneous contrast enhancement. In some cases, lymphocytic hypophysitis has been reported to show a cystic appearance [15,16]. Thus, there are many variations of MRI features of lymphocytic hypophysitis.…”
Section: Case Reportmentioning
confidence: 99%